Contração dinâmica máxima prévia retarda fadiga nos músculos vasto lateral e medial durante exercício de força submáximo - Rocha, Mateus Alves (2022)
Introduction: The resistance training session is important to improve strength levels, hypertrophy and sports performance. However, an efficient session refers to an appropriate conditioning activity. In this context, the post-activation potentiation mechanism emerges, which is configured as a temporary improvement in muscle performance due to a conditioning activity. Objective: To analyze the acute effect of the influence of conditioning activity at 100% of 1RM on fatigue delay in the vastus lateralis and medial muscles when requested at 80% of 1RM until concentric fatigue. Methodos: Eleven male subjects were submitted to two protocols: a) experimental and b) control. At the experimental moment, the individuals performed an acute conditioning activity with 100% of 1RM and in the control moment this load was 0% of 1RM, followed respectively by performing the squat with 80% of 1RM, in the 2020 cadence until concentric fatigue. Results: When comparing the average number of repetitions between the different moments, no statistically significant differences were found. When analyzing the contraction time of the different moments, it was observed that it was statistically shorter in the control group. During the comparison of the values referring to myoelectric activation by the RMS, it was noticed that there was no significant difference between the moments in both muscles. Finally, no significant difference was observed in the median frequency values in the vastus lateralis muscle with and without conditioning activity, but there were significant differences in the first and fourth repetitions of the vastus medialis muscle. Conclusions: Maximum conditioning activity at 100% of 1RM was not able to delay fatigue in men trained during exercise at 80% of 1RM. The conditioning activity of 1RM increased the number of repetitions and the contraction time, suggesting the possibility of improving performance.